COMPARISON OF CFD SIMULATION WITH 3 TURBULENCE MODELS FOR BREASTSHOT PICO HYDRO TURBINE - Dendy Adanta (Universitas Sriwijaya, 2020)
The breastshot waterwheels are suitable for low head condition because it offers a stable efficiency compared to other types of turbine. In some cases, computational fluid dynamics (CFD) was utilized to predict the performance, geometry optimization or physical phenomena of a breastshot waterwheel, CFD offers easiness in terms of energy, time and cost than doing experimental test. Turbulence modeling is a mathematical method to approach the evolution of turbulence. The aim of this study is to identify the suitable turbulence model for a breatshot waterwheel. These three turbulence models were utilized: k-? standard, k-? scalable near wall function and SST k-?. The braking preloads in simulation was varied, which were 75 N m, 150 Nm, 225 N m and 300 N m. Based on grid convergence index (GCI), the 123k elements of mesh and timestep size of 0.002 s were used and when compared to the exact value, an error below 2% was found. Moreover, the k-? scalable near wall function model and the turbulent SST k-? model give the similar result in torque. Therefore, the simulation test to find torque will be more efficient if using the standard k-? turbulent model because it has computational time which is lower than the turbulent SST k-? model. For the eddy viscosity and turbulence intensity contour k-? standard turbulent model and k-? near wall scalable gives no significant differences, but SST k-? model doe. The simulation test to find eddy viscosity and turbulence intensity contour will be more accurate if using SST k-? model, because this model has the mean rate-of-rotation tensor function, ? , and the blending functions, that makes SST k-? model have better accuracy on the near wall calculation.